Multidimensional Community Empowerment Based on Participatory Action Research in Rajeg Village, Tangerang: Pemberdayaan Masyarakat Multidimensi Berbasis Participatory Action Research di Desa Rajeg, Tangerang - Za'in Fuad Hariri; Nabilla Az-Zahra; Muhamad Farhan; Nabil Sayyida Legawa; Fitri Wulandari; Faradillah Dwi Rahayu; Ika Khoerotul Inayah; Farhan Ferdiansyah; Ardan Abimanyu; Asya Putri Tifana; Basyir Abdullah; Zahira Ramadhania; Lulu Wahyuni; Kemala Muliawati; Muhammad Rizki Fadillah; Muhammad Naufal Fadhail; Rina Sari; Diva Nafilah (Yayasan Cerdas Pedia Indonesia, 2025)
The Community Service Program (KKN) Team 207 Pranadipa Paramita in Rajeg Village, Tangerang Regency, employed a Participatory Action Research (PAR) methodology to empower the community across five key domains: education, religion, social cohesion, health, and environment. Iterative phases of participatory planning, collaborative action, observation, and reflection ensured interventions aligned with local needs and assets. In education, initiatives included tutoring, creative literacy sessions, and ecoprint workshops to foster creativity and environmental awareness. Religious and nationalistic activities, such as children’s recitation groups and Independence Day celebrations, effectively strengthened social cohesion and communal solidarity. Environmental innovations hydroponic training and Ecoplang installations with waste-sorting facilities increased household food security and waste management practices. Evaluation outcomes indicated improved academic capacity, active community engagement, and sustained behavioral change. Recommendations include forming hydroponic farming groups and formalizing youth organizations to sustain the programs. This study confirms that PAR is an effective approach for achieving sustainable, multidimensional community empowerment.